Math, asked by Bhawanikumawat, 1 year ago

prove that : tan theta /1-cot theta +cot theta /1-tan theta =1+sec theta cosec theta.

Answers

Answered by rohitkumargupta
1063
HELLO DEAR,



GIVEN:- tanθ/(1 - cotθ) + cotθ/(1 - tanθ)

=> tanθ/(1 - 1/tanθ) + (1/tanθ)/(1 - tanθ)

=> tan²θ/(tanθ - 1) - 1/tanθ(tanθ - 1)

=> 1/(tanθ - 1) { tan²θ - 1/tanθ }

=> 1/(tanθ - 1) { (tan³θ - 1)/tanθ)

[as, a³ - b³ = (a - b)(a² + b² + ab)

=> {(tanθ - 1)(tan²θ + 1 + tanθ)}/{(tanθ - 1)(tanθ)}

=> tanθ + cotθ + 1

=> sinθ/cosθ + cosθ/sinθ + 1

=> (sin²θ + cos²θ)/sinθ . cosθ + 1

=> 1/sinθ . cosθ + 1

=> cosecθ . secθ + 1



I HOPE IT'S HELP YOU DEAR,
THANKS
Answered by Anonymous
329

GIVEN:-

 \sf  \frac{ \tan \theta}{1 -  cot\theta }  +  \frac{  \cot \theta}{ 1 -  \tan \theta}  = 1 +  \sec \theta \cosec  \theta

TO FIND:-

 \tt lhs = rhs

SOLUTION:-

 \tt lhs \ratio  -

 \sf  \frac{ \tan \theta}{1 -  cot\theta }  +  \frac{  \cot \theta}{ 1 -  \tan \theta}

 \tt  =  \frac{ \frac{ \sin \theta  }{ \cos\theta } }{1 -  \frac{\cos\theta}{\sin \theta}  }  +    \frac{\frac{\cos\theta}{\sin \theta}  }{1 - \frac{ \sin \theta  }{ \cos\theta }}

 \tt =   \frac{ \frac{ \sin \theta  }{ \cos\theta } }{ \frac{ \sin \theta- \cos\theta}{  \sin \theta}  }  +    \frac{\frac{\cos\theta}{\sin \theta}  }{ \frac{  \cos\theta  -  \sin \theta  }{ \cos\theta }}

 \tt  =  \frac{ \sin \theta   }{ \cos \theta  }  \times  \frac{ \sin \theta  }{(\sin \theta - \cos \theta )   }  +  \frac{\cos \theta }{\sin \theta}  \times \frac{  \cos  \theta  }{( \cos  \theta -   \sin \theta )   }

 \tt =  \frac{  { \sin}^{2}\theta}{ \cos \theta( \sin \theta -  \cos \theta)  }  -  \frac{ { \cos }^{2}  \theta }{ \sin \theta( \sin \theta -  \cos \theta )    }

 \tt  =  \frac{1}{( \sin \theta  -  \cos \theta) } [ \frac{ { \sin}^{2}  \theta }{ \cos \theta  }  -  \frac{ { \cos }^{2}  \theta}{ \sin \theta  } ]

 \tt  =  \frac{1}{( \sin \theta  -  \cos \theta) } [    \frac{ { \sin}^{3  } \theta -  { \cos }^{3} \theta  }{ \sin \theta \cos \theta  }  ]

 \tt  =  \frac{1}{( \sin \theta  -  \cos \theta) } [   \frac{( \sin \theta -  \cos \theta)( { \sin}^{2}  \theta +  { \cos }^{2}    \theta +  \sin \theta \cos \theta )}{ \sin \theta \cos \theta    }   ]

 \tt  = \frac{(1 +  \sin \theta \cos \theta)}{( \sin \theta \cos \theta)}  =  \frac{1}{ \sin \theta \cos \theta  }  +  \frac{( \sin \theta \cos \theta)   }{( \sin \theta \cos \theta)  }

 =  \sec \theta \cosec \theta + 1

 = rhs

Similar questions